A global framework of mountain ecology - Körner, Christian (Nepalese Journal of Zoology, 2022)
In this contribution, I will summarize a number of features of mountain ecosystems that apply globally. After providing a brief statement on mountain definitions and some mountain statistics, I will recall the major climatic and atmospheric drivers and how their action is modified by geomorphology and type of vegetation. I will close by highlighting the power of sharp microenvironmental gradients in mountains to test ecological hypothesis and elaborate projections on future developments in a global warming context.